Facing Terrorism Alone - Carolyn S. Wilken (EDIS)
The threats of terrorism have left us all fearful and anxious. American’s stress level is up and people talk about being anxious and afraid. We worry about the possibility of another terrorist attack. We feel stressed because we don’t know what to expect from day to day. This is a particularly difficult time for older adults who live alone. While older adults have family and friends to turn to, there are times when it is just scary to live alone. It can be especially frightening when you are an older adult. This document is FCS9199, one of a series of the Department of Family, Youth and Community Sciences, Florida Cooperative Extension Service, IFAS, University of Florida, Gainesville FL 32611. First published: May 2003.